2015
DOI: 10.5089/9781513591353.001
|View full text |Cite
|
Sign up to set email alerts
|

What Really Drives Public Debt: A Holistic Approach

Abstract: This paper presents a novel approach to detail the propagation of shocks to public debt. The modeling technique involves a structural vector auto-regression (SVAR) estimator with an endogenous debt accumulation equation. It explores how the main drivers of sovereign debt dynamics-the primary balance, the interest rate, growth and inflation-interact with each other. Such analysis is particularly useful for debt sustainability analysis. We find that some interactions exacerbate the impact of shocks to the accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Bittencourt (2015) applying panel data estimators for a group of new democracies in Latin America as well as Cherif and Hasanov (2012) using a VAR model with debt feedback established unambiguous debt reduction effect of growth. However, Anaya and Pienkowski (2015) and Brafu-Insaidoo et al (2019) found positive effects of growth on public debt movements in the short run.…”
Section: Determinants Of Government Debtmentioning
confidence: 91%
See 1 more Smart Citation
“…Bittencourt (2015) applying panel data estimators for a group of new democracies in Latin America as well as Cherif and Hasanov (2012) using a VAR model with debt feedback established unambiguous debt reduction effect of growth. However, Anaya and Pienkowski (2015) and Brafu-Insaidoo et al (2019) found positive effects of growth on public debt movements in the short run.…”
Section: Determinants Of Government Debtmentioning
confidence: 91%
“…Mimicking Sims (1980) Favero and Giavazzi (2007), Cherif and Hasanov (2012), and Anaya and Pienkowski (2015), we must place restrictions [6] on matrix A in order to make impulse response and forecast error variance decomposition analyses using SVAR framework. Theoretical guidance and empirical judgment could help formalize some kind of causal relationships among variables within the system which in turn facilitates the identification process.…”
Section: Structural Var Identificationmentioning
confidence: 99%
“…A number of studies have been conducted on the determinants of public debt and current account balance in both developed and developing economies (e.g. Cherif and Hasanov, 2012;Bittencourt 2013;Anaya and Pienkowski, 2015;Sisay and Kotosz, 2020;Hashem and Fahmy, 2019;Brafu-Insaidoo et al, 2019;Calderon et al, 2007;Das, 2016;Teamrat, 2018;Sadiku et al, 2015). This paper highlights at least three important differences compared with those studies on low-income economies including Ethiopia.…”
Section: Introductionmentioning
confidence: 86%
“…Accordingly, Models (1), ( 2), ( 5) and ( 6) include the first-order lag of debt because the effect of debt on privatisation could be delayed. Models (3), ( 4), ( 7) and ( 8) also include the first-order lag of debt because one year's debt level is affected by the previous year's level of debt (Anaya & Pienkowski, 2015). Furthermore, Models (3), ( 4), ( 7) and ( 8) include the first-order lag of privatisation variables because the effect of privatisation on debt could be delayed.…”
Section: Models Of Analysismentioning
confidence: 99%